Oralité et échec programmé du manifeste-pétition Not In Our Name (NION) - Simone RINZLER (E-REA)
Thispaper examines the production of a pre-petition-manifesto NIONThe Pledge of Resistance, sung in demonstrations and shows organised by NION (Not In Our Name), a group fighting the hypothesis of a future war in Iraq in Spring 2002. It contributes to the study of the non-fictional genre of the political manifesto by analysing the orality of the genre and by stating its low value as a common and garden variety of manifesto. The voice expressed here does not believe much in the force of language. It is a factor in the erosion of the pragmatic political value of the manifesto as a genre dedicated to a call for action, thanks to a speech act. Knowing that the war in Iraq is imminent and cannot be prevented, the action at stake here is reduced to a mere signature of The Statement of Conscience. The pragmatic aim of the signatories is to claim their dissensus in the political space and to refuse being considered as consenting to an unjust war to be waged in their names. The manifesto song The Pledge of Resistance is a claim to refuse being named as part of the “Authors” of the future war. The signatories refuse to see the war being endorsed by all the citizens of the Nations‑Statespreparing the “War on Terror” in Iraq.